2020
DOI: 10.3390/md18110538
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Effects of Polysaccharides from Spirulina platensis In Vivo and Vitro and Their Activation Mechanism on RAW246.7 Macrophages

Abstract: In this study, Spirulina platensis (S.p.) polysaccharide (PSP) was obtained by ultrasonic-microwave-assisted extraction (UMAE) and purified by an aqueous two-phase system (ATPS). Two different methods were applied to purified Spirulina platensis (S.p.) polysaccharide (PSP), respectively, due to PSP as a complex multi-component system. Three polysaccharide fractions (PSP-1, PSP-2, and PSP-3) with different acidic groups were obtained after PSP was fractionated by the diethyl aminoethyl (DEAE)-52 cellulose chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 37 publications
1
11
1
1
Order By: Relevance
“…The results showed that PSP was nontoxic to splenocytes, which was indicated by constant cell viability at concentrations less than 10 µg/mL and tended to significantly increase at concentrations of 10 mg/mL and 20 mg/mL. This study supports the results reported by Wu et al (2020) that PSP increases splenocyte proliferation. a,b,c,d,e Different notation shows statistically significant difference (p<0.05) Among the two polysaccharides, PSP showed the highest activity on splenocyte proliferation.…”
Section: Splenocytes Proliferationsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that PSP was nontoxic to splenocytes, which was indicated by constant cell viability at concentrations less than 10 µg/mL and tended to significantly increase at concentrations of 10 mg/mL and 20 mg/mL. This study supports the results reported by Wu et al (2020) that PSP increases splenocyte proliferation. a,b,c,d,e Different notation shows statistically significant difference (p<0.05) Among the two polysaccharides, PSP showed the highest activity on splenocyte proliferation.…”
Section: Splenocytes Proliferationsupporting
confidence: 88%
“…In vitro immunostimulator test conducted by Wu et al (2020) showed that polysaccharides of S. platensis (PSP) were shown to increase the proliferation of splenocytes and macrophages as well as increase the production of nitric oxide (NO), TNF-α, and interleukin 6 (IL-6). Suyono et al (2016; have successfully explored and identified mixed microalgae from Glagah Beach, Yogyakarta, Indonesia, hereinafter referred to as the Glagah consortium microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the concentrations of PAP-1 at 800 μg/mL and 1600 μg/mL were a little high, which caused toxic effects on RAW264.7 cells. Most studies have shown that the polysaccharide components isolated and purified from plant polysaccharides can promote cell proliferation in a suitable concentration range (Excessively low concentration of plant polysaccharide may not significantly improve cell activity, while excessive concentration may cause toxicity to cells and inhibit cell proliferation) [ 10 , 48 , 49 ]. This study was consistent with the above research results.…”
Section: Resultsmentioning
confidence: 99%
“…At present, researchers on PAP have made progress in the separation, purification, and determination of chemical structure and biological activity, but there are still many problems to be solved. Most studies have been based on crude polysaccharides, but crude polysaccharides may contain multiple mixed sugar components and small molecular impurities, so it is difficult to obtain a definitive conclusion from these studies [ 6 , 7 , 8 ] In addition, there have been some studies on the structure of isolated and purified PAP by FT-IR, NMR, and GC-MS, but research on the structure has not been thorough enough [ 5 , 9 , 10 ]. The detailed structure of polysaccharides was the foundation for studying their potential mechanisms and structure-activity relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Secara in vitro, polisakarida menunjukkan efek imunostimulan dengan cara meningkatkan produksi oksida nitrat (NO) dan aktivitas makrofag sel RAW246.7 berupa protein sitokin (IL-6, IL-10, TNF-ᾳ) yang meningkatkan fagositik. Makrofag berperan sebagai pemicu respon imun bawaan dan menginduksi respon imun adaptif dalam menanggapi infeksi mikroorganisme patogen (Riccio & Lauritano, 2020;Wu et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified